2017
DOI: 10.1016/j.aju.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrolithotomy in complete supine flank-free position in comparison to prone position: A single-centre experience

Abstract: ObjectivesTo assess the outcomes of performing percutaneous nephrolithotomy (PCNL) in a modified supine position, more feasible for surgeons, anaesthetists, and operating theatre staff, as well as for the patient himself, and evaluating it in comparison to the standard prone position.Patient and methodsA retrospective, case-control study was conducted between January 2011 and December 2015. In all, 197 patient’s records were reviewed. The initial 101 patients were operated upon in prone position. From mid-2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
6
16
1
Order By: Relevance
“…Based on the stone locations, more than half of the subjects in both groups were diagnosed with staghorn calculi. This finding was different from previous studies stating that staghorn calculi were not commonly found [10,11]. However, this does explain the relatively low stone-free rate in this study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Based on the stone locations, more than half of the subjects in both groups were diagnosed with staghorn calculi. This finding was different from previous studies stating that staghorn calculi were not commonly found [10,11]. However, this does explain the relatively low stone-free rate in this study.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to the results of previous studies, there were no significant outcome differences between the supine and prone groups. In terms of the operative time and stone-free rate, Jones et al [10] and Sohail et al [11] found that the supine position was superior to the prone position. However, it is worth noting that in both studies the staghorn calculi prevalence was less than 50%.…”
Section: Resultsmentioning
confidence: 99%
“…arteriovenous fistula, pneumothorax adjacent, visceral injury, or death in either sector. There was no statistically significant difference and this was in agreement with our study (17). Wang et al found that the operation period was much shorter in the prone than in the modified supine posture sector.…”
Section: Table (1): Patients Demographic Datasupporting
confidence: 93%
“…Therefore, a sample size of 100 was taken consisting of 50 patients as group A and 50 as group B. This was also comparable to the sample size calculated by OpenEpi™ sample size calculator by obtaining means and standard deviations of a similar study performed (12).…”
Section: Methodsmentioning
confidence: 86%
“…These adverse effects included changing of patient position causing unnecessary delay, risk of damage to patient's neck, limbs, nerves and eyes; not to forget the least favorable position in morbidly obese patients and those with compromised cardiopulmonary system (2). These outcomes resulted in experimentation of PCNL procedure and thus, supine PCNL was invented by Another retrospective study by Sohail et al (12) conducted from January 2011 to December 2015 on 197 patients showed that the mean operative time in supine PCNL was 32.3+6.6 min shorter than that in the prone position (p<0.001). They also noted that the mean hospital stay was 1.2+0.75 days shorter for the supine vs the prone position (p<0.001).…”
Section: Discussionmentioning
confidence: 99%